„In the Mirror of Things” – Introduction - Kita, Jarosław; Korybut-Marciniak, Maria; Agnieszka Gralak (In the Mirror of Things, 2022)
The next, tenth jubilee volume of the publishing series Private Life of Poles in the 19th Century, similarly to the previous volumes, was also born out of the need for a different story about the past. This time we propose a new cognitive perspective of the private life and everyday life of the epoch – its view – through the prism of people’s material surroundings. Privacy „in the Mirror of Things”, that is focusing attention on the material environment in which the life of Poles under the partitions passed, allowed for the introduction of individual private worlds, showing scenes and the rhythm of everyday life, cultural landscapes, living spaces that remained in the shadows. Objects surrounding a person can be analyzed through the prism of their usefulness, typology, genesis, and territorial scope. Traditional studies of material culture have often lost the social context of artifacts. It is worth looking at their role in a broader perspective. Seemingly silent objects, collected by life, surrounding a person, selected, protected, rejected, constitute a mirror that can speak with an appropriate set of questions. The world of things surrounding a person reflects the reality of his daily existence, his mentality, standard of living, professed values, aesthetic preferences, family ties, the nature of everyday activities, ways of spending free time, group membership, attitude to fashion, religion, and civilization changes.The editors are aware that the presented volume is not exhaustive and only provokes further discourse on the private life of Poles in the 19th century. The prism of „things” opened up an additional spectrum of research possibilities in the sphere of everyday and intimate life of Polish society under the partitions. The articles did not reflect on the mentality of the people of the era to which the door was opened by material sources. The forms surrounding Poles in the nineteenth century made it possible to observe changes within culture, made it possible to penetrate into inaccessible social environments, and the presentation of biographies through „things” shed new light on the figures studied so far only through written sources. „The Mirror of Things” may become an inspiration for further studies on Polish society during the partitions.